Implementation Of The Problem Based Learning (Pbl) Learning Model In The Subject Of Physical Education, Sports And Health (PJOK) At Sd Negeri 1 Lanbaw, Gisting District, Tanggamus District - Rohmah, Mutia Nur Rohmah; S, Lungit Wicaksono; Kurniawan, Candra; Priyono, Dwi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research aims to describe the implementation of the Problem Based Learning (PBL) learning model in physical education, sports and health (PJOK) subjects at SD Negeri 1 Lanbaw. This research is a qualitative descriptive study. The subjects of this research were school principals, PJOK teachers, goods treasurers or facilities and infrastructure supervisors, library managers, grade 5 teachers, grade 4 teachers and female students at SD Negeri 1 Lanbaw. The data collection techniques used were observation, interviews and documentation. The main instrument is the researcher who uses observation guidelines and interview guidelines. This research uses the Miles and Huberman model of data analysis which includes three stages. Namely data reduction, data display, and drawing conclusions. The results of this research can be concluded that the implementation of the problem based learning (PBL) learning model in the subject (PJOK) has not been implemented well. The various obstacles faced are the lack of facilities and infrastructure and learning media in schools, as well as the students who are still adapting.